THE MECHANISM OF BACTERIOSTASIS - Churchman, John W. (The Rockefeller University Press, 1923)
1. Between Gram-positive and Gram-negative organisms gentian violet exhibits the same type of selective activity whether the dye be added to the media on which the bacteria are planted unstained (extrinsic bacteriostasis), or the organisms be stained with it before being planted on plain agar (intrinsic bacteriostasis). In both instances the Gram-positives are inhibited and the Gram-negatives unaffected. 2. Between Gram-positive spore-bearing aerobes and the commoner Gram-negative bacteria, acid fuchsin, related sulfonic substances, and the flavines exhibit one type of selective activity when the dye is added to the media (extrinsic bacteriostasis) and the opposite type when it is added directly to the bacteria (intrinsic bacteriostasis). In the former case, the Gram-positive spore bearers are inhibited and the Gram-negatives unaffected; in the latter case the Gram-negatives are inhibited and the Gram-positive spore bearers unaffected. 3. Selective bacteriostasis is not necessarily conditioned by selective penetrability. Stained organism may grow, and dyes which do not stain well may inhibit reproduction. 4. There is evidence that the phenomena of bacteriostasis may be due to changes effected by the dye at the surface of the organisms.